Effects of oxidizing species on ablation behavior of C/C-ZrB2-ZrC-SiC composites prepared by precursor infiltration and pyrolysis. Issue 16 (December 2016) - Yang, Xin; Su, Zhean; Huang, Qizhong; Chang, Xin; Fang, Cunqian; Chen, Lei; Zeng, Guang
Abstract: C/C-ZrB2 -ZrC-SiC composites are fabricated by precursor infiltration and pyrolysis process with polycarbosilane, ZrB2 and ZrC polymeric precursors. The oxyacetylene and plasma torches are used as two oxidizing flames to investigate the ablative properties of C/C-ZrB2 -ZrC-SiC composites at high temperatures. The C/C-ZrB2 -ZrC-SiC composites exhibit good ablation resistance under the O2 and H2 O+O2 dominated atmospheres. Due to the different oxidizing species and temperatures generated by the two flames, the composites reveal different ablation rates, morphologies and mechanisms. After the oxyacetylene torch test, a molten ZrO2 -SiO2 film formed in the ablation center, whereas a porous stacking layer is present under the plasma flame. The formation of the protecting layers can effectively reduce the inward diffusion of oxygen and heat transfer into the substrate, enabling the C/C-ZrB2 -ZrC-SiC composites to have good ablation resistance at 2300 and 3000 °C.